Reversible manipulation of the magnetic state in SrRuO3 through electric-field controlled proton evolution - Li, Zhuolu; Shen, Shengchun; Tian, Zijun; Hwangbo, Kyle; Wang, Meng; Wang, Yujia; Bartram, F. Michael; He, Liqun; Lyu, Yingjie; Dong, Yongqi; Wan, Gang; Li, Haobo; et al. (Nature communications, 2020)
Ionic substitution forms an essential pathway to manipulate the structural phase, carrier density and crystalline symmetry of materials via ion-electron-lattice coupling, leading to a rich spectrum of electronic states in strongly correlated systems. Using the ferromagnetic metal SrRuO 3 as a model system, we demonstrate an efficient and reversible control of both structural and electronic phase transformations through the electric-field controlled proton evolution with ionic liquid gating. The insertion of protons results in a large structural expansion and increased carrier density, leading to an exotic ferromagnetic to paramagnetic phase transition. Importantly, we reveal a novel protonated compound of HSrRuO 3 with paramagnetic metallic as ground state. We observe a topological Hall effect at the boundary of the phase transition due to the proton concentration gradient across the film-depth. We envision that electric-field controlled protonation opens up a pathway to explore novel electronic states and material functionalities in protonated material systems. Ionic substitution is a useful way to manipulate structural, electronic, magnetic phase transitions in strongly correlated materials. Here, the authors report electric-field controlled protonation in SrRuO 3 , resulting in a large structural expansion and a ferromagnetic-to-paramagnetic phase transition.